Market Reaction of the Indonesian Banking Sector to the Announcement of MSCI Index Rebalancing Suspension - Muhammad Wildan Purnama; Nur Kholidah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
This study looks into how Indonesian banking stocks reacted to the January 28, 2026, announcement that the MSCI Index rebalancing would be suspended. Using a 15-day observation window that included 7 trading days prior to and 7 trading days following the announcement, an event research methodology was employed. Purposive sampling was used to select the 15 banking companies listed on the IDX.